The political economy of public sector governance - Bertelli, Anthony Michael (Cambridge : Cambridge University Press, 2012)
'In The Political Economy of Public Sector Governance, Anthony Michael Bertelli introduces core ideas in positive political theory as they apply to public management and policy. Though recent literature that mathematically models relationships between politicians and public managers provides insight into contemporary public administration, the technical way these works present information limits their appeal. This book helps readers understand public-sector governance arrangements and the implications these arrangements have for public management practice and policy outcomes by presenting information in a non-technical way'--
'Democracy means rule by the people. In a democracy, administration must be constructed in such a way that it serves the people through their elected representatives. The connection between the public and any given administrative action may be quite distant, but it must be in place. Accountability of public management to the popular will may be weak or attenuated, but the arrangements might be justified on other grounds. In any event, the problem of connecting the public with administration must be confronted. It is quite possible that some members of the polity, fully believing in the democratic process, disagree with an administered decision that is without democratic defect. In other words, even with democratic accountability, what government produces may not be the policy that you want'--
Includes bibliographical references (p. 185-197) and index.
Keywords: Public administration; Government accountability